Developing a Learning Model to Promote the Skills of Analytical Thinking - Harto Nuroso; Joko Siswanto; Choirul Huda (Intelektual Pustaka Media Utama, 2018)
This research is aimed at developing a learning model that encourages the skills of analytical thinking in science. The method used is research and development. The result is the ICAE (Incubation, Collection of data, Analysis, and Evaluation) model that promotes analytical thinking skills. Results of normalized gain tests show that the gain score is 0.28, which indicates that the ICAE learning model positively affects students’ analytical thinking, even though still within the lower category. The ICAE model also promotes the skills of analytical thinking in science and it has gained positive response from students.